Resistance Training - Part 2: Considerations in Maximizing Sport Performance - Plisk, S. (coachesinfo.com)
Basic exercises are exactly that - basic. In general, they are very straightforward and there is little need to substitute other movements in their place or supplement them with different types of assistance exercises intended to target the muscles differently. This is not a concrete rule, however, and some prudent alternatives are offered below. Long-term variety is often best achieved by adjusting the workload for a limited number of movements rather than attempting to include every possible exercise. Commonly used exercises include squats, pulling movements and presses. Considering the concept of "basic exercise", strength training exercises can be classified into three categories: 1 Primary or "structural" ...multi-joint, weight bearing (e.g., weightlifting movements, squat, deadlift). 2 Secondary or "supplemental" ...multi-joint, non-weight bearing (e.g., upper-body pressing or pulling exercises). 3 Tertiary or "isolation" ...single-joint, non-weight bearing. Primary exercises are movements, which by definition tend to yield the most profound results; whereas those further down the continuum have lesser effects, and are usually technically simpler. The examples cited above for each category are certainly not comprehensive, and it is not difficult to create hybrid movements. For example, weightlifting movements in which explosive impulse and power are the fundamental objectives represent a special case of primary exercises that are semi-ballistic in nature. The lunge and step-up each meet the criteria for a primary exercise; whereas machines such as a hip sled or leg press arguably do not, despite the fact that they may involve similar muscle mass and exertion. In fact, the latter may be viable options during extremely intensive workloads and/or the athlete's trunk cannot safely support the weight required to train the legs in movements such as the squat or deadlift (as discussed below). The chin-up/pull-up, dip, push-up and related exercises can be considered multi-joint weight-bearing movements, which would place them in the primary category according to this scheme. However, they often receive less emphasis than the traditional upper-body exercises mentioned above. Furthermore, they usually do not involve the same muscle mass or resistance used in other primary movements, making it difficult to justify placing them in the same group. All things considered, however, they may deserve greater consideration than "standard" upper-body movements. There are other examples as well, but the point is that this classification scheme is not an attempt to label certain movements as being good or bad. It is simply a place to start making rational decisions about selecting and prioritizing them. As is the case with all aspects of a program, principles should be used as a guide rather than preferences. Perhaps most importantly, this means that training effect has precedence over strength demonstration. The objective is to choose the most effective movements and execute them in the most beneficial way.